Get FINED! - Cheong, Cheryl Wei Lin (2015)
Get FINED is Singapore’s first campaign to encourage financial literacy among Singapore undergraduates through the use of creative expression. This strategic communications campaign is organised by four final-year undergraduates from the Wee Kim Wee School of Communication and Information at Nanyang Technological University. Singapore introduced the first national financial education programme in 2003. Despite numerous initiatives by financial and tertiary institutions, a worrying 90% of young adults are reportedly unprepared for their financial future and are lacking in personal financial management. The team decided to investigate and address this lack of financial understanding with an effective communications campaign targeted at young adults — Get FINED. Through the use of creative expression and dialogue, Get FINED aims to highlight the urgency of being financially literate, rebrand financial knowledge and encourage financial literacy to jolt undergraduates to take action in financial planning. The report outlines the campaign’s formative research, strategies and details the campaign programming and execution. The report also extends into quantitative and qualitative evaluations of the campaign’s impact and output objectives. The campaign achieved significant success in engaging with undergraduates with 98.59% of the participants finding the Get FINED campaign to be relevant to them. The report also discusses the implications of the campaign findings for future financial education for undergraduates, as well as recommendations for the sustainability and expansion of this campaign. Appendices supplement the report with detailed survey processes, charts, and photographs for further references.